PENERAPAN MODEL PEMBELAJARAN GENERATIF LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMA NEGERI 5 PEKANBARU - Gadis Safitri; Betty Holiwarni; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Objective of this study is to improve the learning outcomes of students and is to look the effect of it on the subject of solubility and constant solubility product (Ksp) through an application of learning models Generative Learning in class XI IPA SMAN 5 Pekanbaru. The conducted research type is quasi experimental study using Design Randomized Control Group Pretest-Posttest.. The subject of this study was all of the students of Class XI IPA SMAN 5 Pekanbaru. Samples from this study was students of class XI IPA2 as experimental class and class XI IPA1 as control class, this sample was randomly selected using Cluster Random Sampling Tecnique. Experimental class was given experimental treatment using Generative Learning Model, while the control class was treated using usual method dicussion. Based on the results of research, mean scores in experimental class was 84,38, while control class was 79,02. From hypothesis testing data analysis obtained t>ttable ie 2.17>1.67 and based on analysis data using logistic regression obtained value of 7,5%. It means the use of learning model generative learning could improve learning outcomes of student on the subject solubility and constant solubility product (Ksp) in class XI IPA SMAN 5 Pekanbaru with effect of 7,5%.Key Words: Generative Learning, Results Learning, Solubility and Constant SolubilityProduct (Ksp)